Nuances in Genioplasty - Minehart, Bailey R.; Barrera, Jose E. (Facial Plastic Surgery, 2025)
The goal of the article is to help surgeons understand the anatomy and surgical technique of alloplastic and osseous genioplasty.The article provides a brief history of cosmetic osseous genioplasty and the rise of alloplastic genioplasty after the 1950s.This study describes the vertical thirds of the face with anatomic landmarks and the zero meridian assessment for chin deficiencies.Use of virtual surgical planning for custom genioplasty advancements and hardware and the ultrasonic bone saw for bony cuts.This article also describes how to evaluate patients for genioplasty and determine if alloplastic or osseous genioplasty will result in the best patient desired outcome, including the degree of advancement desired, any change in vertical height, correction in horizontal asymmetry, or reduction of the chin.The surgical technique is described for both osseous and alloplastic genioplasty. An intraoral approach is described for osseous genioplasty, while external and intraoral is described for alloplastic.Brief discussion of postoperative care, including compressive dressings, postoperative edema, and duration of liquid diet.Improvement of custom planning with virtual surgical plans as well as development of implants with low risk of infection and extrusion.This study summarizes the anatomic importance of genioplasty with the advantages and disadvantages of osseous and alloplastic genioplasty.
Keywords: osseous genioplasty; alloplastic genioplasty; chin implant; microgenia